2022
DOI: 10.3389/fpls.2022.835306
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study Reveals the Genetic Basis of Five Quality Traits in Chinese Wheat

Abstract: Bread wheat is a highly adaptable food crop grown extensively around the world and its quality genetic improvement has received wide attention. In this study, the genetic loci associated with five quality traits including protein content (PC), gluten content (GC), baking value (BV), grain hardness (HA), and sedimentation value (SV) in a population of 253 Chinese wheat grown in Inner Mongolia were investigated through genome wide association mapping. A total of 103 QTL containing 556 SNPs were significantly rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 66 publications
5
8
0
Order By: Relevance
“…Two QTL hotspots (3B.5 and 4B.5) were in similar positions to those reported by Yang et al (2019) in a Chinese winter wheat collection, but they did not share common traits. The study reported by (Hao et al, 2022) also with a collection of Chinese breeding lines that shared three regions, 2B.1, 3D.1, and 4B.5, although the last one reported an association with yield in our study. Finally, when comparing our results with (Rathan et al, 2022), using a diverse panel including breeding lines, landraces, and synthetic lines, four common regions were observed: 1A.2, 3B.3, 3B.5, and 5B.1.…”
Section: Marker Trait Associationssupporting
confidence: 67%
“…Two QTL hotspots (3B.5 and 4B.5) were in similar positions to those reported by Yang et al (2019) in a Chinese winter wheat collection, but they did not share common traits. The study reported by (Hao et al, 2022) also with a collection of Chinese breeding lines that shared three regions, 2B.1, 3D.1, and 4B.5, although the last one reported an association with yield in our study. Finally, when comparing our results with (Rathan et al, 2022), using a diverse panel including breeding lines, landraces, and synthetic lines, four common regions were observed: 1A.2, 3B.3, 3B.5, and 5B.1.…”
Section: Marker Trait Associationssupporting
confidence: 67%
“…A genome-wide association study (GWAS) is an effective approach to identify genomic regions associated with specific variants of complex traits, which could dissect more alleles compared with linkage analysis. Recently, GWAS has been widely used to detect important candidate genes associated with yield, quality, salt stress, and drought stress ( Reig-Valiente et al., 2018 ; Luo et al., 2021 ; Hao et al., 2022 ; Wu et al., 2022 ). In barley, many functional loci associated with agronomic traits ( Xu et al., 2018 ), salt stress tolerance ( Mwando et al., 2020 ), drought stress tolerance ( Tarawneh et al., 2020 ), grain quality ( Jia et al., 2021 ) and disease resistance ( Pan et al., 2022 ) have been identified by GWAS.…”
Section: Introductionmentioning
confidence: 99%
“…Mergoum et al (2013) had found a stable locus of grain hardness at 23 Mb on chromosome 1A, named 2013_Mergoum_3 , which was 4.39 Mb–8.94 Mb away from AX-111028882 identified on chromosome 1A in this study, considered the same site of grain hardness for close distance [ 37 ]. The stable genetic locus of grain hardness was excavated at 42.55–49.23 Mb on chromosome 1A, and the locus qHA1A.1 discovered by Hao et al [ 34 ] at 54.5 Mb were close to each other, so they were considered as the same locus. It was further indicated that 23.00–54.50 MB on chromosome 1A played an important role on controlling grain hardness, which could be the focus of further research.…”
Section: Discussionmentioning
confidence: 99%